Vasectomy and the Risk of Akidah Degradation: A Legal-Theological Analysis of the Boundaries of Ikhtiar in Family Planning - Abdul Wahid; Zaki Saiful Alam; Muhammad Ihsan Nurmizan (Journal of Indonesian Islamic Studies, 2025)
The practice of vasectomy as a permanent contraceptive method is frequently regarded as a pragmatic response to contemporary economic pressures. However, from an Islamic theological perspective, the decision raises significant concerns when it is motivated by fear of poverty and economic insecurity. This article aims to analyze vasectomy through a legal-theological framework, focusing on its jurisprudential status and its implications for the doctrine of aqidah and the belief in Allah’s guarantee of sustenance (rizq). This normative legal study employs philosophical, juridical, and sociological approaches, utilizing content analysis of relevant Qur’anic verses and classical Shafi‘i jurisprudential literature. The study finds that under Shafi‘i jurisprudence, vasectomy as a permanent sterilization method (qat‘u al-nasl) is strictly prohibited (haram). Furthermore, when it is performed primarily on economic grounds (al-sabab al-iqtisadi), it reflects a weakened understanding of tawakkul (reliance upon Allah) and a corrupted belief (al-i'tiqad al-fasid) in Allah’s name as al-Razzaq (the Provider). The Qur’an emphasizes that the provision of sustenance for all creatures is guaranteed by Allah, as stated in QS. Hud [11]: 6 and QS. Adh-Dhariyat [51]: 22–23. Consequently, the permanent termination of fertility due to economic anxiety is not merely a medical or demographic issue but also raises profound theological questions concerning faith, reliance upon divine providence, and the objectives of Islamic family law. The findings of this article highlight the importance of greater harmonization between national reproductive health policies and Islamic theological principles as an effort to preserve both the welfare and spiritual integrity of society amid the growing influence of sociological materialism.